Geologi Daerah Buyat Dan Sekitarnya, Kecamatan Kotabunan, Kabupaten Bolaang Mongondow Timur, Provinsi Sulawesi Utara - Deden, Mokoagow Deden; Kasim, Muhammad; Hutagalung, Ronal; Akase, Noviar (Universitas Negeri Gorontalo, 2023)
This research focuses on the eastern part of the northern arm of Sulawesi to understand the geological conditions, including geomorphology, lithology, stratigraphy, and geological structure. The goal is to determine the geological history and map the geological conditions to identify potential mineral resources. The research methods include a qualitative approach through field observations such as morphology, outcrop descriptions, lithology, geological structure measurements, stratigraphic relationships, as well as an inventory of natural resources and geological disaster risks. The quantitative approach involves calculations and analyses, including geomorphological analysis, petrography, paleontology, geological structure, stratigraphy, and the reconstruction of geological history. The research results identify four geomorphological units (karst, denudational, volcanic, alluvial) and six geological units at the research site. Andesite and volcanic breccia are the oldest units dating back to the Miocene. At the end of the Miocene, uplift and subsidence formed intrusive hills of diorite and limestone. Volcanic activity ceased in the Miocene. In the Pliocene, sandstone formed due to river transport. The rock formation process continues to the present, with alluvial deposit units resulting from the breakdown of rocks around the lake. Geological structure analysis reveals fault lines with the main stress direction from northwest to southeast. Relative fault data indicates fault inclination values suggesting the main stress direction is northwest-southeast. The geological history in the research area began in the Miocene with magmatism and tectonic activities, forming andesite and volcanic breccia units. This history extends to the formation of alluvial deposit units in the present. The research provides in-depth insights into the geological history and potential mineral resources in the region, serving as a foundation for further research.